The effect of trust, customer satisfaction and image on customers’ loyalty in Bank Islam Ipoh, Perak Darul Ridzuan / Nurul Huda Mohamad Jaffar - Mohamad Jaffar, Nurul Huda (2010)
This research attempts to find the factors of customer loyalty and their relationships in Bank Islam Ipoh. In order to do this, a questionnaire is designed and validated, then based on the data which is gained from the sample of 80 respondents’ that volunteered to complete multiple self-administered questionnaire for the data collection process, the analysis is done and the results and the relations among the factors are explained. Data was then aggregated and analyzed using descriptive analysis, and correlation. Trust, customers’ satisfaction and image are the factors that influence customers’ loyalty of the customers in Bank Islam in this study. These factors also influence each other as well. The relationships of different factors with each other are also studied and the SPSS software is used to analyze the data gathered from the respondents. From the study, it was found that most of the customers in Bank Islam had experienced high level in customers’ loyalty whereas others considered as moderate. Besides that, trust and customers’ satisfaction was positively significant towards customers’ loyalty in Bank Islam Ipoh. The results demonstrate that most of the customers are trusted and satisfied, however the possibility of customers dissatisfied of the banks always exists.